2019
DOI: 10.1136/bmjopen-2018-025906
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a quasi-experimental study of the effectiveness and cost-effectiveness of mother and baby units compared with general psychiatric inpatient wards and crisis resolution team services (The ESMI study) in the provision of care for women in the postpartum period

Abstract: IntroductionResearch into what constitutes the best and most effective care for women with an acute severe postpartum mental disorder is lacking. The effectiveness and cost-effectiveness of psychiatric mother and baby units (MBUs) has not been investigated systematically and there has been no direct comparison of the outcomes of mothers and infants admitted to these units, compared with those accessing generic acute psychiatric wards or crisis resolution teams (CRTs). Our primary hypothesis is that women with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…This was a mixed-methods secondary data analysis of the ESMI (Effectiveness of perinatal mental health services) study. ESMI was a quasi-experimental cohort study embedded within existing service matrices, examining the effectiveness and cost effectiveness of psychiatric mother and baby units (MBU), compared with general psychiatric inpatient wards and crisis resolution teams (CRT) for mothers with psychiatric illness in the first postpartum year ( 23 ). The study obtained NHS Research Ethics Committee approval from the London-Camber well St. Giles committee (number: 14/LO/0765) and this secondary data analysis was conducted in accordance with the Declaration of Helsinki and General Data Protection Regulations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a mixed-methods secondary data analysis of the ESMI (Effectiveness of perinatal mental health services) study. ESMI was a quasi-experimental cohort study embedded within existing service matrices, examining the effectiveness and cost effectiveness of psychiatric mother and baby units (MBU), compared with general psychiatric inpatient wards and crisis resolution teams (CRT) for mothers with psychiatric illness in the first postpartum year ( 23 ). The study obtained NHS Research Ethics Committee approval from the London-Camber well St. Giles committee (number: 14/LO/0765) and this secondary data analysis was conducted in accordance with the Declaration of Helsinki and General Data Protection Regulations.…”
Section: Methodsmentioning
confidence: 99%
“…Short- and long-term follow-up assessments were undertaken at one- and 12-months post-discharge from psychiatric services. Detailed description of recruitment methods and study procedures can be found in the study protocol ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…We have recently completed the first study using a quasi‐experimental design to examine the effectiveness and cost‐effectiveness of mother and baby units compared with generic acute psychiatric wards or crisis resolution teams (teams available daily providing intensive treatment at home) 207 . Analysis is underway to examine the effectiveness of mother and baby units in reducing readmission rates and other outcomes, including improving quality of mother‐infant interactions one month after discharge.…”
Section: Service Deliverymentioning
confidence: 99%
“…For a full list of measures used see Trevillion et al (2019). This study draws its findings from the Perinatal VOICE (PV) questionnaire, a 27-item, self-report questionnaire, an adapted version of a service-user designed measure of views of acute care (Evans et al, 2012).…”
Section: Data Collectionmentioning
confidence: 99%